2003
DOI: 10.1590/s0104-42302003000100029
|View full text |Cite
|
Sign up to set email alerts
|

Hiperpigmentação cutânea em pacientes com insuficiência renal crônica em hemodiálise infectados pelo vírus da hepatite C

Abstract: RESUMO -OBJETIVO. A hiperpigmentação cutânea é comumente encontrada em pacientes portadores de insuficiência renal crônica (IRC), sendo também uma das manifestações mais evidentes da Porfiria Cutânea Tarda (PCT). Essa doença, que tem sido relatada em pacientes em hemodiálise (HD), tem como um dos fatores precipitantes a infecção pelo vírus da hepatite C (HCVportante desencadeador de um distúrbio do metabolismo das porfirinas que pode se expressar clinicamente por esse sintoma [5][6][7][8] . O objetivo deste es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 9 publications
(18 reference statements)
1
1
0
1
Order By: Relevance
“…Although the patients in the two studies were different in terms of the cultural context, they are in agreement with each other in terms of achieving similar results (4). Similarly, the results of a study by Choi et al indicated an increase in hyperpigmentation in renal patients treated with hemodialysis, which is in agreement with the findings of the present study (15). However, Pico et al (9) showed that hyperpigmentation decreased with increasing dialysis duration, which is in contrast with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Although the patients in the two studies were different in terms of the cultural context, they are in agreement with each other in terms of achieving similar results (4). Similarly, the results of a study by Choi et al indicated an increase in hyperpigmentation in renal patients treated with hemodialysis, which is in agreement with the findings of the present study (15). However, Pico et al (9) showed that hyperpigmentation decreased with increasing dialysis duration, which is in contrast with the results of the current study.…”
Section: Discussionsupporting
confidence: 92%
“…Essas lesões atingem tanto a estrutura quanto a coloração dérmica. 1 Muitas patologias sistêmicas ocasionam manifestações cutâneas, que podem ocorrer antes ou após a manifestação sistêmica. Esses achados são de extrema importância na elucidação diagnóstica.…”
Section: Introductionunclassified
“…A hiperpigmentação difusa foi notada em 22% dos pacientes. 28,10 A hiperpigmentação poderia ser decorrente de elevação da concentração de melanina na camada basal e superficial da derme. Tal fenômeno ocorreria devido ao acúmulo do hormônio estimulador de betamelanócitos (B-MSH), com a diminuição da função renal.…”
Section: Manifestações Cutâneas Nos Pacientes Hemodialisadosunclassified